Determinants of Smartphone Addiction in Indonesian Adolescents: Scoping Literature Review - Liza Marini; Wiwin Hendriani; Primatia Yogi Wulandari (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
The rising popularity of smartphones today, in addition to causing positive impacts on adolescent development, can also negatively affect the adolescents to the point of causing smartphone addiction. Therefore, it is crucial to find out the different factors that potentially trigger smartphone addiction. This study will investigate the determinant factors that affect smartphone addiction in Indonesian Adolescents. Using scoping literature review, the following procedures were carried out: establishing research protocol, identification, selection, data extraction based on inclusion criteria as well as the analysis, and reporting the results. 19 out of 180 articles were selected through 3 electronic databases, namely Google Scholar, Garuda Portal, and Microsoft academic. The results showed that both internal and external factors determined smartphone addiction in Indonesian Adolescents. Internal factorsof self-regulation, self- esteem and FoMo, gender, loneliness, cyberloafing, self- control, self-regulated learning and mindfulness, while external factors consisted of family functioning, ease of use and social anxiety, parental roles, academic stress as well as family and peer attachment. However, because of the variety of factors, it is not yet known which factors have the most impact on smartphone addiction. The implication of this study can be utilized by policy makers and practitioners to minimize the prevalence of smartphone addiction in Indonesian adolescentssuch ascombining internal and external factors in designing an intervention development module related to smartphone addiction in Indonesian adolescents. Additionally, the gaps found in this study can provide clues for future studies on smartphone addiction in Indonesian adolescents.